Purkinje Cardiomyofiber Sarcocystosis: Does It Cause Fatality? – Mini Review - N. Babu Prasath; J. Selvaraj (The Indian Veterinary Journal, 2023)
Cardiac malady due to Purkinje cardiomyofiber sarcocytosis in a goat as reported as reported is reviewed. A two year old adult goat carcass was presented for postmortem examination to Department of Veterinary Pathology, Veterinary College and Research Institute, Orathanadu, Thanajvur with a history of sudden death after a brief period of constipation. Systematic postmortem examination of carcass was carried out. Heart revealed scattered endocardial ecchymosis of the left ventricle. Histopathologically, Purkinje fibers showed Sarcocystis species encysted with thin wall. Sarcocysts were irregular in shape with tightly packed bradyzoites. Sarcocysts in affected Purkinje fibers occupied the entire cell with pressure atrophy to the surrounding Purkinje fibers. No inflammatory reaction was evidenced. Variable hypothesis were documented regarding the altered Purkinje fibers and its possible pathological effects in humans and animals. Though incidence of sarcocytosis in Purkinje fibers were reported in domestic and wild animals, its effect on cardiac conduction has not been studied. Ventricular tachycardia (fibrillations) was reported to be the cause of Purkinje fiber dysplasia in cat and myocardial sarcocytosis in humans. Based on the published background, the present case was discussed with possible anatomy, physiology and Purkinje fiber sarcocystosis.